Reconstruction of Photon Conversions in the MPD Experiment - Evgeny Kryshen; Dmitry Ivanishchev; Dmitry Kotov; Mikhail Malaev; Victor Riabov; Yuriy Ryabov (Particles, 2021)
Spectra of thermal photons carry important information on the temperature of the hot and dense medium produced in heavy ion collisions. Photons can be measured via their conversion into electron-positron pairs in the detector material. In this contribution, challenges in the photon reconstruction are discussed and feasibility studies on photon conversion measurements in the future multipurpose detector (MPD) experiment at NICA are presented. The obtained results indicate good prospects for thermal photon measurements.